Stereotactic Body Radiation and Interleukin-12 Combination Therapy Eradicates Pancreatic Tumors by Repolarizing the Immune Microenvironment - Mills, Bradley N. (Cell Rep, 2019)
Over 80% of pancreatic ductal adenocarcinoma (PDA) patients are diagnosed with non-resectable late-stage disease that lacks effective neoadjuvant therapies. Stereotactic body radiation therapy (SBRT) has shown promise as an emerging neoadjuvant approach for treating PDA, and here, we report that its combination with local interleukin-12 (IL-12) microsphere (MS) immunotherapy results in marked tumor reduction and cures in multiple preclinical mouse models of PDA. Our findings demonstrate an increase of intratumoral interferon gamma (IFNγ) production following SBRT/IL-12 MS administration that initiates suppressor cell reprogramming and a subsequent increase in CD8 T cell activation. Furthermore, SBRT/IL-12 MS therapy results in the generation of systemic tumor immunity that is capable of eliminating established liver metastases, providing a rationale for follow-up studies in advanced metastatic disease.